2021
DOI: 10.3390/s21196488
|View full text |Cite
|
Sign up to set email alerts
|

Firmware Update Using Multiple Gateways in LoRaWAN Networks

Abstract: The remarkable evolution of the IoT raised the need for an efficient way to update the device’s firmware. Recently, a new process was released summarizing the steps for firmware updates over the air (FUOTA) on top of the LoRaWAN protocol. The FUOTA process needs to be completed quickly to reduce the systems’ interruption and, at the same time, to update the maximum number of devices with the lowest power consumption. However, as the literature showed, a single gateway cannot optimize the FUOTA procedure and of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The authors of [27] extended the FUOTAsim simulator [8] to study a LoRaWAN scenario. Firmware updates were carried out using multiple gateways instead of one.…”
Section: Simulations and Models For Lora Environmentsmentioning
confidence: 99%
“…The authors of [27] extended the FUOTAsim simulator [8] to study a LoRaWAN scenario. Firmware updates were carried out using multiple gateways instead of one.…”
Section: Simulations and Models For Lora Environmentsmentioning
confidence: 99%
“…Application notifications: IoT application servers may need to relay information to end devices, such as decisions based on result analysis or some commands to modify sampling intervals. Remote firmware update: firmware updates are used to enhance the deployed IoT application in terms of security, fix bugs in the existing firmware, and add more functionalities [17]. The Firmware Update Over The Air (FUATA) [18] is one of the first proposed solutions for a remote firmware update in LoRaWAN.…”
Section: Technology Overviewmentioning
confidence: 99%
“…The performance of LoRaWAN scenarios in the presence of both uplink and downlink communication has been investigated and analyzed by many researchers in the literature [17,[19][20][21][22]. The works in [19][20][21] concluded that downlink traffic has a significant impact on the overall performance of LoRaWAN.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation